The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1809-4430-eng.agric.v41n5p559-566/2021
|View full text |Cite
|
Sign up to set email alerts
|

Dem Simulation and Experiment of Corn Grain Grinding Process

Abstract: To improve the working performance of hammer mill, cutting-edge hammer and oblique hammer were designed in this study. The advantages of new hammers were theoretically analyzed. The grinding process of corn grain with different hammers was studied by discrete element method (DEM) and experiments. Discrete element simulation results showed that under same rotor speed conditions, the cutting-edge hammer had highest bond-breaking efficiency in corn grain model. The oblique hammer could reduce the incident angle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Similarly, Vukmirovic et al [15] compared the effects through two different grinding methods, and their result showed that materials were more uniform in size after grinding by roller mill but generally had a larger diameter; this was quite contrary for the hammer mill. Wang et al [16] designed a pointed hammer and a bevel-faced hammer. The DEM analysis revealed that using the pointed hammerhead would improve the productivity of hammerhead mill.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Vukmirovic et al [15] compared the effects through two different grinding methods, and their result showed that materials were more uniform in size after grinding by roller mill but generally had a larger diameter; this was quite contrary for the hammer mill. Wang et al [16] designed a pointed hammer and a bevel-faced hammer. The DEM analysis revealed that using the pointed hammerhead would improve the productivity of hammerhead mill.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study did not delineate a specific method for multiobjective optimization. Wang and colleagues [12] endeavored to enhance the operational efficiency of the hammer mill by designing hammer blades with both tip and slant hammer shapes. They utilized a blend of the discrete element method (DEM) and experimental techniques to explore the crushing processes of corn particles using different hammerheads.…”
Section: Introductionmentioning
confidence: 99%
“…In China, scientific research institutions and related enterprises, such as Foton Lovol, Wuzheng Group, and Yongmeng Company, have done a lot of research on corn grain combine harvesters, and have had good field test results in various provinces. However, due to the high grain moisture content of corn harvested in my country, there is still serious kernel damage (Feng et al, 2019, Chen, 2020, Wang, 2021.…”
Section: Introductionmentioning
confidence: 99%